Does Vitamin D Provide Added Benefit to Antihypertensive Therapy in Reducing Left Ventricular Hypertrophy Determined by Cardiac Magnetic Resonance?. (26th August 2022) - Levy, Phillip D; Twiner, Michael J; Brody, Aaron M; Dawood, Rachelle; Reed, Brian; Mango, LynnMarie; Gowland, Laura; Grandits, Greg; Svendsen, Kenneth; Haacke, Ewart Mark; Li, Tao; Zhang, Liying; et al.
Abstract: BACKGROUND: Left ventricular hypertrophy (LVH) and vitamin D deficiency have been linked to hypertension (HTN) and cardiovascular disease, particularly in African Americans (AAs). Our objective was to determine if the addition of vitamin D to antihypertensive therapy would lead to greater regression of LV mass index (LVMI) as determined by cardiac magnetic resonance (CMR) after 1 year in vitamin D deficient AA patients with uncontrolled HTN and LVH. METHODS: This study was a randomized, double-blind, placebo-controlled, single-center study. AA patients with HTN (systolic blood pressure [BP] >160 mm Hg), increased LVMI, and vitamin D deficiency (<20 ng/ml) were randomized. All patients received antihypertensive therapy combined with biweekly 50, 000 IU vitamin D3 (vitamin D group, n = 55) or placebo (placebo group, n = 58). RESULTS: At 1 year, there were no statistical differences between the vitamin D and placebo groups in LVMI (−14.1 ± 14.6 vs. −16.9 ± 13.1 g/m 2 ; P = 0.34) or systolic BP (−25.6 ± 32.1 vs. −25.7 ± 25.6 mm Hg; P = 0.99) reduction, respectively. Serum vitamin D levels increased significantly in the vitamin D group compared with placebo (12.7 ± 2.0 vs. 1.8 ± 8.2 ng/ml; P < 0.001). CONCLUSIONS: In this high-risk cohort of AAs we did not find an association between vitamin D supplementation and differential regression of LVMI or reduction in systolic BP. However, our study suffered from a small sample size with low statistical power precluding a definitive conclusion on the therapeutic benefit of vitamin D in such patients. CLINICAL TRIALS REGISTRATION: Trial Number NCT01360476. Full trial protocol is available from corresponding author. Graphical Abstract: